Quality assessment of GNSS with short-length session in the displacement measurement of a large embankment dam - Lima, J. N. (2016)
After a large set of GNSS tests carried out on a 325 m baseline, with different length observation sessions, we assessed the quality of GNSS with short-length sessions to monitoring the displacements of a large embankment dam, in south of Portugal. The GNSS campaigns were performed at the same time of classic geodetic observation campaigns, with Leica TCA2003 tacheometer and Leica NA2 optical level, and the results were compared: the standard deviations of the differences of the two methods for horizontal and vertical displacements were 3.6 mm and 5.7mm, respectively. These values are in agreement with those which we obtained on a 325 m baseline with GNSS using sessions of 5 minutes length. The results of this test show that the GNSS with short-length sessions has enough precision to monitoring large embankment dams.